Curriculum 2013 Based on The Philosophy Perspective of Progressivism - Noviyanti, Ika Nurma (Journal of Mathematics and Mathematics Education, 2019)
It should be understood that curriculum is the heart of education. The education curriculum in Indonesia has undergone various changes which are based on refining the previous curriculum as well as the 2013 Curriculum which synchronizes the previous curriculum. The philosophical foundation used in designing the curriculum is very important in determining educational goals. The results of the research show that the 2013 Curriculum can increase changes in knowledge, attitudes, and skills towards students for the realization of better character education. The 2013 curriculum has a goal of giving birth to an active, innovative and creative generation that aims to reduce ignorance, poverty and underdevelopment in life. The 2013 curriculum has a philosophical basis that adopts a foreign philosophy or is called an inclusive eclectic which is then synchronized with the Indonesian national education system. Progressivism is an educational philosophy that focuses on a process, where the 2013 Curriculum in theory focuses more on students. The 2013 curriculum illustrates if students must get learning that is in accordance with the development of the times in order to give birth to a generation of reformers and every competency in students is assessed as a whole both knowledge, attitudes, and skills.